2020
DOI: 10.1038/s41598-020-57633-3
|View full text |Cite
|
Sign up to set email alerts
|

Reference gene validation for quantification of gene expression during ovarian development of turbot (Scophthalmus maximus)

Abstract: Quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) is a powerful and sensitive method used in gene expression analysis. Suitable reference genes, which are stable under all experimental circumstances and tissues significantly improve the accuracy of qRT-PCR data. In this study, the stability of six genes, namely, 18S ribosomal RNA (18s), beta-actin (actb), elongation factor 1-alpha (ef1α), glyceraldehyde-3-phosphate-dehydrogenase (gapdh), cathepsin D (ctsd), and beta-2-microglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…As previously reported, the rankings of the most stable reference genes assessed via different software manifested similarity to a certain extent, but slight discrepancies due to adopting of various algorithms also occurred [62]. For example, in the pituitary of turbot, the results of geNorm demonstrated that actb and ctsd were the most suitable reference genes, and the optimal candidates assessed by Normfinder were actb and b2m, whereas in accordance BestKeeper analysis, 18S was the most appropriate reference gene [67]. Consistently, in this study, the three software all proposed 18S as the most suitable candidate in GPS cells under normal physiological conditions; regarding GPHK cells, in the light of results generated by BestKeeper or geNorm, the optimal reference genes were RPL13 and RPL13/18S, respectively, whereas UBCE was evaluated as the most stable reference gene according to NormFinder.…”
Section: Discussionsupporting
confidence: 55%
“…As previously reported, the rankings of the most stable reference genes assessed via different software manifested similarity to a certain extent, but slight discrepancies due to adopting of various algorithms also occurred [62]. For example, in the pituitary of turbot, the results of geNorm demonstrated that actb and ctsd were the most suitable reference genes, and the optimal candidates assessed by Normfinder were actb and b2m, whereas in accordance BestKeeper analysis, 18S was the most appropriate reference gene [67]. Consistently, in this study, the three software all proposed 18S as the most suitable candidate in GPS cells under normal physiological conditions; regarding GPHK cells, in the light of results generated by BestKeeper or geNorm, the optimal reference genes were RPL13 and RPL13/18S, respectively, whereas UBCE was evaluated as the most stable reference gene according to NormFinder.…”
Section: Discussionsupporting
confidence: 55%
“…RT-qPCR is a commonly used method to study changes in gene expression due to its capacity of relative quantification of gene expression. It is always necessary to find at least one or better multiple individually tested reference genes for each cell type through experimental condition considering the error susceptibility and sensitivity of this method 35 .…”
Section: Discussionmentioning
confidence: 99%
“…ACTB was reported to be used for qPCR profiling of tissue‐specific gene expression in half‐smooth tongue sole (Li et al ., 2010) and blotched snakehead ( C. maculata ) (Mao et al ., 2017). GAPDH is considered a favourable reference gene in common carp ( Cyprinus carpio ) (Shi et al ., 2016), turbot ( Scophthalmus maximus ) (Gao et al ., 2020) and embryonic zebrafish ( D. rerio ) (Liu et al ., 2018). 18 S was also rated as the most stable reference gene in many fish tissues (Wang et al ., 2018; Liu et al ., 2014; Small et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%